A Numerical Investigation of the Characteristics of Seismic Signals Induced by Rockfalls - Feng, Zheng-Yi; Shen, Zhao-Ru; Zhuang, Rui-Chia (Frontiers in Earth Science, 2021)
This study proposes a numerical coupling approach to simulate seismic signals of rock falls and conducts a parameter analysis to explore the characteristics of the seismic signals generated by rockfalls. To validate the approach, three field rockfall tests were selected for comparison. The rockfall velocity, duration, seismic frequency, Husid plot, Arias intensity and spectrogram of the seismic signals were compared. We found that friction between rocks and the ground affects rock falling behavior. In addition, the local damping and Rayleigh damping assignments in the numerical model have strong effects on the simulation results. The volume of the falling rock and the falling speed of the rock affect the Arias intensity. The coupling approach proposed could be extended and can potentially be used as a useful tool in rockfall hazard estimations.